2018
DOI: 10.1007/s10585-018-9914-x
|View full text |Cite
|
Sign up to set email alerts
|

Editorial: Therapy-induced metastasis

Abstract: The idea for this Special Issue originated from our recent review in Nature Reviews Clinical Oncology entitled "Does the mobilization of circulating tumour cells during cancer therapy cause metastasis?" Martin et al. (Nat Rev Clin Oncol 14:32-44, 2017). While preparing this review, it became evident that an overwhelming number of preclinical and clinical papers were implicating the involvement of all the major and indispensable cancer treatment modalities in causing increased numbers of tumour cells in circula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 22 publications
(27 reference statements)
0
5
0
Order By: Relevance
“…A number of recent preclinical and clinical observations indicate an unexpected involvement of all major cancer treatment modalities in enhancing the number of circulating tumor cells, and as such, potentially inducing distant metastasis (1). With an ever increasing understanding of the molecular complexities and the intertwining circuitries governing the effect of tumor microenvironment on disease progression, it is not surprising that research efforts have focused on uncovering the mechanisms of therapy-driven tumor progression, which may obfuscate the longterm benefits of anticancer therapeutic interventions (2). Therapeutic procedures previously linked to paradoxical promotion of the prometastatic machinery include chemotherapy (3)(4)(5), radiotherapy (6)(7)(8), surgery (9), or even perioperative anesthesia (10).…”
Section: Introductionmentioning
confidence: 99%
“…A number of recent preclinical and clinical observations indicate an unexpected involvement of all major cancer treatment modalities in enhancing the number of circulating tumor cells, and as such, potentially inducing distant metastasis (1). With an ever increasing understanding of the molecular complexities and the intertwining circuitries governing the effect of tumor microenvironment on disease progression, it is not surprising that research efforts have focused on uncovering the mechanisms of therapy-driven tumor progression, which may obfuscate the longterm benefits of anticancer therapeutic interventions (2). Therapeutic procedures previously linked to paradoxical promotion of the prometastatic machinery include chemotherapy (3)(4)(5), radiotherapy (6)(7)(8), surgery (9), or even perioperative anesthesia (10).…”
Section: Introductionmentioning
confidence: 99%
“…In a study of 413 patients with brain metastasis of different causes, Amelot et al27 found that anticancer drugs, especially paclitaxel and its derivatives, promoted brain metastasis and reduce disease-free survival of patients. A recent review suggested that all commonly used treatments, including radiotherapy, chemotherapy, fine-needle puncture, and surgery, can cause an increase in circulating tumor cells and promote cancer progression and distant metastasis 28. Thus, the positive effects of hydrogen inhalation on cancer patients are very encouraging.…”
Section: Discussionmentioning
confidence: 99%
“…Once a hotly debated topic, concerns that cancer treatments could promote its spread have been largely overshadowed by advances in cancer survival. However, now, as cure is becoming a realisable goal for a greater proportion of patients, the extent to which therapies promote cancer is being revisited [1]. Of the many factors at play in therapeutic management, malignant cells shed from primary tumours due to resective procedures are an obvious cause for concern [2].…”
Section: Introductionmentioning
confidence: 99%